a case report Right femur malunion treated with open osteotomy and open reduction with internal fixation percutaneous surgery (ORIF PS): A case report - Pande Putu Agung Willa Kesawa Putra; Anak Agung Ngurah Ronny Kesuma (DiscoverSys Inc., 2022)
Introduction: Fracture femur distal third is a common orthopedic problem in patients of all ages. Malunion is common due to neglected conditions; an osteotomy plus ORIF PS procedure is required in the management. Surgery is currently the treatment of choice for distal femoral malunion fractures. Malunion requires deep fixation of compression using lag screws, cortical screws or cancellous screws depending on the type of fracture. Patients with distal femoral malunion are also treated with grafting using bone graft, allograft, autograft, synthetic graft and blade plate with screws in combination with a safe quadriceps approach. Case description: A 16-year-old female patient complained of unbalanced walking and cramps in the right leg for the last 3 months. The patient had a history of traffic accidents and then suffered femur fracture 9 months ago, debridement and a plaster cast. The physical examination found that the right leg was shorter than the left, and the AVN and active ROM distal right leg were still good. Then X-Ray examination obtained the results of his Malunion fracture of the middle 1/3 right femur and then decided to do an osteotomy + ORIF PS. The patient returned home in good condition and then controlled through the outpatient polyclinic. Conclusion: In most malunion patients, osteotomy and PS ORIF are surgical methods. Corrective osteotomy with ORIF PS should be regarded as a salvage procedure for treating distal third malunion.